Significant aspects in relation to agile usage: Malaysian perspective - Asnawi, Ani Liza; Gravell, Andrew M.; Wills, Gary B. (2014)
Agile methods are an established process for developing software nowadays. There is, however, less evidence on their usage among software practitioners in Malaysia. While the methods have become mainstream in other regions, that is not the case in this country. This paper investigates important aspects in relation to Agile usage in Malaysia. The study was conducted using a questionnaire with 207 software practitioners from the country. Non parametric analysis (Chi-Square test) was conducted to investigate the relationship of Agile usage with (i) language, (ii) place of education and (iii) organization types. Results showed Agile usage has significant association with the two aspects; (i) language and (ii) organization types. It is suggested that these two aspects must be taken into consideration if one organization plans to adopt the methods. The results also revealed that many of the Agile users are not being exposed to the method before they start using it. We aim to provide knowledge and evidence on the suitability of Agile methods to the people in the country and nearby region.